Strategi Implementasi Pelimpahan Kewenangan Bupati kepada Camat di Kabupaten Sidoarjo Jawa Timur - Hadi, Asmara (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This paper describes and analyzes the implementation of delegated authority to the Head of the county Sidoarjo Regent and Implementation Strategy. Data obtained from all stakeholders discussion group delegated authority to the Head of the Regent and the report documents the results of Monitoring and Evaluation of the Implementation Delegation of Authority to the Head of Regents from 2011 to 2015. Based on the analysis of this study concluded that the implementation of the Delegation of Authority Sidoarjo regent to the county district head has not run optimally it is seen from the four factors correspond Policy Implementation Model by George Edward III, Resource, Disposition, Bureaucratic Structure and communication has not been optimally applied.